Endoscope-assisted fluorescence-guided resection allowing supratotal removal in glioblastoma surgery - Bettag, Christoph; Schregel, Katharina; Langer, Philip; Thomas, Carolina; Behme, Daniel; Stadelmann, Christine; Rohde, Veit; Mielke, Dorothee (Neurosurgical focus, 2021)
OBJECTIVE Several studies have proven the benefits of a wide extent of resection (EOR) of contrast-enhancing tumor in terms of progression-free survival (PFS) and overall survival (OS) in patients with glioblastoma (GBM). Thus, gross-total resection (GTR) is the main surgical goal in noneloquently located GBMs. Complete tumor removal can be almost doubled by microscopic fluorescence guidance. Recently, a study has shown that an endoscope with a light source capable of inducing fluorescence allows visualization of remnant fluorescent tumor tissue even after complete microscopic fluorescence-guided (FG) resection, thereby increasing the rate of GTR. Since tumor infiltration spreads beyond the borders of contrast enhancement on MRI, the aim of this study was to determine via volumetric analyses of the EOR whether endoscope-assisted FG resection enables supratotal resection beyond the borders of contrast enhancement. METHODS The authors conducted a retrospective single-center analysis of a consecutive series of patients with primary GBM presumed to be noneloquently located and routinely operated on at their institution between January 2015 and February 2018 using a combined microscopic and endoscopic FG resection. A 20-mg/kg dose of 5-aminolevulinic acid (5-ALA) was administered 4 hours before surgery. After complete microscopic FG resection, the resection cavity was scanned using the endoscope. Detected residual fluorescent tissue was resected and embedded separately for histopathological examination. Nonenhanced and contrast-enhanced 3D T1-weighted MR images acquired before and within 48 hours after tumor resection were analyzed using 3D Slicer. Bias field-corrected data were used to segment brain parenchyma, contrast-enhancing tumor, and the resection cavity for volume definition. The difference between the pre- and postoperative brain parenchyma volume was considered to be equivalent to the resected nonenhancing but fluorescent tumor tissue. The volume of resected tumor tissue was calculated from the sum of resected contrast-enhancing tumor tissue and resected nonenhancing tumor tissue. RESULTS Twelve patients with GBM were operated on using endoscopic after complete microscopic FG resection. In all cases, residual fluorescent tissue not visualized with the microscope was detected. Histopathological examination confirmed residual tumor tissue in all specimens. The mean preoperative volume of brain parenchyma without contrast-enhancing tumor was 1213.2 cm. The mean postoperative volume of brain parenchyma without the resection cavity was 1151.2 cm3, accounting for a mean volume of nonenhancing but fluorescent tumor tissue of 62.0 cm. The mean relative rate of the overall resected volume compared to the contrast-enhancing tumor volume was 244.7%. CONCLUSIONS Combined microscopic and endoscopic FG resection of GBM significantly increases the EOR and allows the surgeon to achieve a supratotal resection beyond the borders of contrast enhancement in noneloquently located GBM.
Gesehen am 05.02.2021